Economic Feasibility of Traditional Market Development in The Archipelago Area On Sebuku Island, South Kalimantan - Surti; Mohammad Adhiya Riswandha; Chairul Abdi; Muhammad Firmansyah; Gusti Ihda Mazaya (Jurnal Ilmu Ekonomi JIE, 2026)
This study analyzes the economic feasibility of Sebuku Market development through demand-side analysis in a disadvantaged archipelago region of South Kalimantan. Using a cross-sectional survey design with 262 respondents through stratified random sampling, the research employs multiple linear regression to identify spatial demand determinants. Results reveal exceptionally high public support (a 97% approval rate) and strong shopping interest (a mean score of 4.52/5.0). The regression model demonstrates excellent explanatory power (R² = 0.717, F = 71.342, p < 0.001), with seven market attributes and two control variables significantly influencing demand. Product quality exhibits the highest elasticity (β=0.243), followed by service quality (β=0.221), price affordability (β=0.198), and physical infrastructure (β=0.189). The distance variable shows negative elasticity (β = -0.112), confirming the presence of spatial constraints. Economic projections indicate annual turnover of Rp60 billion, aggregate income multiplier effect of Rp16.3 billion/year, and benefit-cost ratio of 1.63 in year one. The study validates market infrastructure as an effective growth pole for inclusive regional development, providing evidence-based policy recommendations to optimize investment in archipelagic contexts.